Activated learning; providing structure in global health education at the David Geffen School of Medicine at the University of California, Los Angeles (UCLA)– a pilot study. Issue 1 (December 2016) - Jordan, Jaime; Hoffman, Risa; Arora, Gitanjli; Coates, Wendy
Abstract Background Global health rotations are increasingly popular amongst medical students. The training abroad is highly variable and there is a recognized need for global health curriculum development. We sought to create and evaluate a curriculum, applicable to any global health rotation, that requires students to take an active role in their education and promotes engagement. Methods Prospective, observational, mixed method study of 4th year medical students enrolled in global health courses at UCLA in 2011–12. Course directors identified 4 topics common to all rotations (traditional medicine, health systems, limited resources, pathology) and developed activities for students to complete abroad: observation, interview and reflection on resources, pathology, medical practices; and compare/contrast their experience with the US healthcare system. Students posted responses on a discussion board moderated by US faculty. After the rotation, students completed an anonymous internet-based evaluative survey. Responses were tabulated. Qualitative data from discussion board postings and free response survey items were analyzed using the framework method. Results 14 (100 %) students completed the Activated Learning assignment. 12 submitted the post rotation survey (85.7 %). Activated Learning enhanced GH education for 67 % and facilitated engagement in the local medical culture for 67 %. Qualitative analysis of discussion board posting demonstrated multiple areas of knowledge gain and analysis of free response survey items revealed 5 major themes supporting Activated Learning: guided learning, stimulation of discussion, shared interactions, cultural understanding, and knowledge of global healthcare systems. Increased interactivity emerged as the major theme for future improvement. Conclusion The results of this study suggest that an Activated Learning program may enhance education, standardize curricular objectives across multiple sites and promote engagement in local medical culture, pathology and delivery systems. Increased interaction between students and faculty may augment the impact of such a program.